2022
DOI: 10.3390/ijms232214029
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor IAA27 Positively Regulates P Uptake through Promoted Adventitious Root Development in Apple Plants

Abstract: Phosphate (P) deficiency severely limits the growth and production of plants. Adventitious root development plays an essential role in responding to low phosphorus stress for apple plants. However, the molecular mechanisms regulating adventitious root growth and development in response to low phosphorus stress have remained elusive. In this study, a mutation (C-T) in the coding region of the apple AUXIN/INDOLE-3-ACETIC ACID 27 (IAA27) gene was identified. MdIAA27T-overexpressing transgenic apple improved the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Numerous studies have confirmed that auxin plays a key role in AR formation [ 13 , 38 , 39 , 40 , 41 ]. SAUR is the largest gene family with auxin-responsive factors [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed that auxin plays a key role in AR formation [ 13 , 38 , 39 , 40 , 41 ]. SAUR is the largest gene family with auxin-responsive factors [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, AtIAA8 interacted with the TIR1 auxin receptor and ARF TFs, involved in lateral root formation (Arase et al, 2012). The TF MdIAA27, the homologous gene of RHC12H1G0553.2, positively regulates phosphate uptake by promoting adventitious root development in apple (Zhao et al, 2022). It is speculated that heat stress may regulate root development through IAA signal transduction pathway and then affect plant growth.…”
Section: Degs and Detfs Involved In Heat Stress Responsementioning
confidence: 99%
“…LBD TFs harbor an N-terminal lateral organ boundary (LOB) domain and play a crucial role in regulating organ development in plants, among which lateral root development is prominent [ 30 , 31 ]. For example, MdARF26 and MdARF27 upregulate the expression of MdLBD16 to increase the length and number of adventitious roots under low Pi stress [ 32 ].…”
Section: Introductionmentioning
confidence: 99%